Safety and feasibility of initiating a hepatic artery infusion pump chemotherapy program for unresectable colorectal liver metastases: A multicenter, retrospective cohort study. Issue 1 (23rd October 2020) - Muaddi, Hala; D'Angelica, Michael; Wiseman, Jason T.; Dillhoff, Mary; Latchana, Nicholas; Roke, Rachel; Ko, Yoo‐Joung; Carpizo, Darren; Spencer, Kristen; Fields, Ryan C.; Williams, Gregory; Aucejo, Federico; et al.
Abstract: Introduction: Hepatic artery infusion pump (HAIP) chemotherapy is a specialized therapy for patients with unresectable colorectal liver metastases (uCRLM). Its effectiveness was demonstrated from a high volume center, with uncertainty regarding the feasibility and safety at other centers. Therefore, we sought to assess the safety and feasibility of HAIP for the management of uCRLM at other centers. Methods: We conducted a multicenter retrospective cohort study of patients with uCRLM treated with HAIP from January 2003 to December 2017 at six North American centers initiating the HAIP program. Outcomes included the safety and feasibility of HAIP chemotherapy. Results: We identified 154 patients with HAIP insertion and the median age of 54 (48–61) years. The burden of disease was >10 intra‐hepatic metastatic foci in 59 (38.3%) patients. Patients received at least one cycle of systemic chemotherapy before HAIP insertion. Major complications occurred in 7 (4.6%) patients during their hospitalization and 13 (8.4%) patients developed biliary sclerosis during follow‐up. A total of 148 patients (96.1%) received at least one‐dose of HAIP chemotherapy with a median of 5 (4–7) cycles. 78 patients (56.5%) had a complete or partial response and 12 (7.8%) received a curative liver resection. Conclusion: HAIP programs can be safely and effectively initiated in previously inexperienced centers with good response.